Pathogenic Role of Complement in Antiphospholipid Syndrome and Therapeutic Implications - Tedesco, Francesco; Borghi, Maria Orietta; Gerosa, Maria; Chighizola, Cecilia Beatrice; Macor, Paolo; Lonati, Paola Adele; Gulino, Alessandro; Belmonte, Beatrice; Meroni, Pier Luigi (Frontiers in Immunology, 2018)
Antiphospholipid (aPL) antibodies act as pathogenic autoantibodies in the antiphospholipid syndrome (APS) being responsible for thrombosis and miscarriages. However, the exact mechanisms of the syndrome are still a matter of investigation. While vascular thrombosis is apparently not associated with inflammation, miscarriages can be explained only in part by the aPL-mediated hypercoagulable state and additional non-thrombotic effects, including placental inflammation, have been described. Despite this difference, evidence obtained from animal and patients studies supports that complement activation is a common denominator. Tissue-bound aPL rather than circulating aPL-beta2glycoprotein I immune-complexes are responsible for the activation of the classical and the alternative complement pathways. The role of complement is supported by the finding that complement-deficient animals are protected from the pathogenic effect of passively infused aPL and similar results have been obtained blocking complement activation. Moreover, elevated levels of complement activation products in the absence of abnormalities in regulatory molecules have been found in APS patients, strongly suggesting that the activation of complement cascade is the result of aPL binding rather than of a defective regulation. Placental complement deposits represent a further marker of complement activation both in animals and in patients, and there is also some suggestive evidence that activation products are deposited in the affected vessels. The aim of this review is to analyse the state of the art of complement involvement in the pathogenesis of APS in order to provide insights into the role of this system as predictive biomarker for the clinical manifestations and as therapeutic target.